(untitled) (Discourse of Law and Administration, 2024)
The study undertakes to present and analyse key issues related to the principles of public property management. The legislator, in view of the need to protect the public interest, defined the principles for the supervision of legal person actions, the subject of which is public property. Due to the fact that public property is used for the performance of public tasks, it should be managed in accordance with the principles of proper economy, with particular care. One of the forms of supervision envisaged by the legislator is the necessity to obtain the consent of a public administration body for the disposal of property. Apart from determining the legal nature of the organ’s consent and the procedure for obtaining it, the subject of analysis will also be the determination of the legal consequences of disposing of property without first obtaining it.